MULTICULTURAL EDUCATION-BASED SOCIAL SCIENCE INSTRUCTIONAL MODEL IN ISLAMIC SCHOOL - Choirul Mahfud (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2019)
Abstract:The Islamic schools in Surabaya participated in teaching on the social-science instructional model based multicultural education. The research aimed to study about how to design the instructional model performed by the teachers then practiced together in the teaching and learning process at the Islamic Schools in Surabaya, and to find out how the teachers’ creativity in managing the class and educating the students to become the generations who has multicultural competencies for the nation progress in maintaining harmony in the religious community. This research used descriptive qualitative method. The research findings showed that the social-science instructional model based multicultural education was implemented to the students in the Islamic schools, especially in understanding the multicultural in the social life.Abstrak:Sekolah Islam di Surabaya berpartisipasi dalam pengajaran model pembelajaran Ilmu Sosial berbasis pendidikan multikultural. Tujuan dari penelitian ini adalah untuk mempelajari bagaimana merancang model pembelajaran yang dilakukan oleh guru kemudian berlatih bersama dalam pengajaran dan pembelajaran di Sekolah Islam di Surabaya dan untuk menemukan bagaimana kreativitas guru dalam mengelola kelas dan mendidik anak-anak untuk menjadi generasi yang kompetensi multikultural untuk kemajuan bangsa dalam menjaga keharmonisan dalam komunitas agama. Penelitian ini menggunakan metode deskriptif kualitatif. Temuan penelitian adalah bahwa model pembelajaran sains sosial berbasis pendidikan multikultural di Sekolah Islam diterapkan kepada siswa, terutama dalam memahami multikultural dalam kehidupan sosial.